Virtual reality-assisted pulmonary rehabilitation enhances early lung function recovery after thoracoscopic surgery in lung cancer patients: a non-concurrent controlled study - Wenjie, Wang; Yifan, Jiang; Li, Wang; Xiaomin, Guan; Linlin, Zhou; Yuhan, Cheng; Sibei, Wan; Fang, Fang (Frontiers in Medicine, 2025)
ObjectiveTo investigate the clinical effectiveness of pulmonary rehabilitation health education and respiratory function training based on virtual reality (VR) technology in promoting early postoperative pulmonary function recovery in patients undergoing thoracoscopic surgery for lung cancer.MethodsA single-center, non-concurrent, pre-post controlled study was conducted. Ninety-five patients who underwent thoracoscopic radical resection of lung cancer between June 2023 and February 2024 were assigned to the control group and received routine postoperative respiratory function education. Another 95 patients admitted between March and December 2024 were assigned to the intervention group and received VR-based health education combined with training guidance. The intervention lasted for 3 days. Outcomes compared between groups included pulmonary function recovery, time to extubation, incidence of postoperative pulmonary complications, satisfaction with health education, and safety of the intervention.ResultsThe compliance rate in the intervention group was 94.74%, significantly higher than that in the control group (85.26%) (p < 0.05). On postoperative day 3, FVC%, FEV1%, MVV, and MVV% were significantly better in the intervention group compared to the control group (p < 0.01). The time to extubation was also significantly shorter in the intervention group (p < 0.01). There was no significant difference in the incidence of pulmonary complications within 7 days after surgery between the two groups (p > 0.05). Patient satisfaction in the intervention group was 91.11%, significantly higher than 72.84% in the control group (p < 0.01). Three mild adverse events were reported during the VR intervention, which were resolved after temporary suspension of the session and did not affect the completion of the intervention.ConclusionVR-based health education combined with postoperative respiratory function training effectively improves patient compliance, promotes early pulmonary function recovery, shortens extubation time, and enhances patient satisfaction. It is clinically safe and feasible and holds promise for broader application in postoperative nursing care for lung cancer patients.